Toward Transparent Governance: A Case Study of Good and Clean Governance Practices within the Office of District Administrators - Rifyansyah, Ramadhan; Iwhan Ariftian Zuhdi, Agus; Suharsono, Yoyok; Suripto, Suripto (International Journal of Applied Finance and Business Studies, 2024)
The Sukolilo Sub-District Administration Office, Surabaya, is committed to realizing transparent and clean governance. This study aims to understand governance practices in the Sukolilo Sub-District Administration Office, identify factors that support or hinder transparency, and explore potential improvements and innovations that can be made. Using a qualitative case study method, data were collected through interviews, observations, and document analysis. The results show that the Sub-District Office has implemented various efforts to improve governance, such as formulating clear vision, mission, and goals, implementing standard operating procedures (SOPs), and improving budget and financial management systems. However, there are still some challenges faced, such as lack of public awareness, limited resources, lack of innovation, and a suboptimal bureaucratic work culture. This study recommends several steps to improve the governance of the Sukolilo Sub-District Office, such as increasing socialization and education, utilizing information technology, increasing cooperation with other parties, strengthening internal and external supervision, and improving a professional work culture..